Model Ekonomi Berbasis Komunitas: Bukti dari Usaha Mikro Kecil Pertanian di Depok - Muhammad Anwar Fathoni; Tasya Hadi Syahputri (Politeknik Negeri Bali, 2025)
This article aims to examine the community-based economic model implemented within the Micro Small Agricultural Enterprises (MSAEs) community in Depok, Indonesia, in response to the city’s stagnant economic development over the past decade. Improving regional economic performance requires more than top-down policies; it demands active participation from the community to stimulate local economic growth. One promising approach is the development of a community-based economic system, where economic actors collaborate to foster self-reliance and sustainability. This study employs a qualitative descriptive approach using a case study method. Both primary data, collected through interviews and observations, and secondary data from relevant documents were utilized in this research. The findings reveal that the community-based economic model in the MSAEs community is built upon three core areas of activity: marketing, education, and social engagement. These areas work in synergy to create an ecosystem that encourages active participation and shared responsibility among members. In the marketing domain, the community plays a crucial role in expanding market access and enhancing the competitiveness of local products. In the education sector, training and capacity-building activities are organized to improve the skills and knowledge of community members. The social aspect reinforces the values of mutual aid and solidarity, fostering social cohesion and long-term sustainability of joint ventures. Through these integrated efforts, the MSAEs community contributes to building a resilient and inclusive people-centered economy. This model demonstrates the potential of community-based economic systems to revitalize local economies and address structural challenges in a post-growth urban context.